2021
DOI: 10.3390/ijerph18031193
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Workplace Conflicts on Self-Reported Medically Certified Sickness Absence in Latvia

Abstract: Sickness absence is one of the most important working population health indicators. It is a complex phenomenon that is investigated by health care and occupational health specialists, economists, and work psychologists. Sickness absence is used as a predictor for morbidity and mortality, but besides the health status of an individual, sickness absence is influenced by demographic, socio-economic factors, and work environment factors. Conflicts at work are a common psychosocial risk factor that can affect sickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…The results of this research show that conflicts with colleagues double the risk of presenteeism, and this is in addition to our previous study showing that they also increase the risk of sickness absence [ 42 ]. Similar findings were revealed in another study regarding intragroup conflicts—a positive correlation was observed both for sickness presenteeism and absenteeism [ 3 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The results of this research show that conflicts with colleagues double the risk of presenteeism, and this is in addition to our previous study showing that they also increase the risk of sickness absence [ 42 ]. Similar findings were revealed in another study regarding intragroup conflicts—a positive correlation was observed both for sickness presenteeism and absenteeism [ 3 ].…”
Section: Discussionsupporting
confidence: 79%
“…This is in line with the findings by Kim et al [ 41 ] that high interpersonal conflicts at work double presenteeism risk even if adjusted for general characteristics (age, gender, marriage status, smoking and drinking habits) and work-related characteristics (permitted sick leave, tenure, position, occupation, shift-work, employment type, and weekly working hours). Furthermore, our previous study about the impact of workplace conflicts on sickness absence pointed to a strong association between these particular types of conflicts and sickness absence [ 42 ]. If the impact of those conflicts on both health behavior outcomes is compared, the odds of presenteeism are significantly higher than those of absenteeism.…”
Section: Discussionmentioning
confidence: 99%
“…Creating a healthy work environment benefits both employees and managers. Employees need to take responsibility for their own well-being by adopting healthy lifestyles, cultivating positive attitudes, and setting achievable goals, while managers need to foster positive environments within their organizations [3,4]. To promote employee well-being, managers can offer rewards, provide constructive feedback, and leverage employees' strengths for the benefit of both the individual and the organization [5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although stress-related disorders are among the leading causes of long-term sickness absence [22], studies that shed light on whether workplace conflicts affect the level of sickness absence among employees are in short supply. We identified only one cross-sectional study of a general working population in Latvia that has reported associations between managers-employee conflicts and self-reported medically certified absence [23].…”
Section: Introductionmentioning
confidence: 99%